2019
DOI: 10.1021/acs.iecr.9b00702
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Theoretical Study on High Pressure Methane Solubility in Natural Deep Eutectic Solvents

Abstract: In this paper, we report high pressure experimental measurements and detailed density functional theory (DFT) as well as molecular dynamic (MD) simulations of methane (CH 4 ) solubility in natural deep eutectic solvents (NADESs) that were prepared by using alanine (Al), betaine (Be), and choline chloride (ChCl) used as hydrogen bond acceptors (HBA) and lactic acid (La), malic acid (Ma), and phenylacetic acid (Paa) used as hydrogen bond donors (HBD). Experiments were performed on Al:La, Be:La, ChCl:La, ChCl:Ma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 96 publications
0
28
0
Order By: Relevance
“…Most stable configurations for HBA and HBD were acquired from the PubChem ® database [71] and were optimized with the theory level that is mentioned in the previous section. This theory level has been selected based on our recent studies [72,73], which was proven for such DES and natural-DES (NADES) systems. The configurations for the HBA-HBD structure are based on the most stable configuration of the studies systems.…”
Section: Resultsmentioning
confidence: 99%
“…Most stable configurations for HBA and HBD were acquired from the PubChem ® database [71] and were optimized with the theory level that is mentioned in the previous section. This theory level has been selected based on our recent studies [72,73], which was proven for such DES and natural-DES (NADES) systems. The configurations for the HBA-HBD structure are based on the most stable configuration of the studies systems.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we studied gas absorption performances via novel NADES, which was obtained by considering choline chloride (ChCl), alanine (Al), and betaine (Be) as HBA, and lactic acid (La), malic acid (Ma), and phenylacetic acid (Paa) as HBD. We showed that these NADES perform very well for CO 2 capture, especially at moderate pressures up to 50 bars, and between 298.15 K and 323.15 K isotherms [49][50][51]. CO 2 sorption experiments showed maximum absorption performance between 3.5 and 5 mmol CO 2 /gr of NADES in these experiments at the highest pressures.…”
Section: Introductionmentioning
confidence: 69%
“…Once the DFT simulations were obtained and the interactions energies were corrected for the BSSE [59], the cases that gave the highest interaction energies were considered for further DFT analysis. In this work B3LYP with the 6-311++G** theory level was selected, based on its accuracy and reasonable computational time [49,50]. The summary of interaction energies for the selected cases are provided in Table 3 in eV units.…”
Section: Resultsmentioning
confidence: 99%
“… No DES Method/Basis Topic of the Publication Reference 1 1-ethyl-3-methylimidazolium chloride: Imidazole Different molar ratios AIMD The BLYP functional with triple-ζ valence polarization basis set and GTH pseudopotentials. CP2K/QUICKSTEP code DFT B3LYP/6-311+G(2d,2p) DES as physical solvents for remarkable separation of H 2 S from CO 2 [ 409 ] 2 1,8-diazabicyclo [5.4.0]undec-7-enium: methylthiourea (4:1) DFT M06e2X/6-311++G(d,p) Dissolution of cellulose in DES [ 339 ] 3 24 choline chloride-based DES with molar ratio from 1:4 to 15:1 DFT B3LYP/6-311G(d,p) B3LYP/def2-SVP def2-SVP/J B3LYP/6-311G(d,p)/def2-TZVP def2-TZVP/J Biomass separation [ 119 ] 4 Alanine:Lactic Acid (1:1) Alanine:Malic Acid (1:1) Betaine:Lactic Acid (1:1) ChCl:Malic Acid (1:1) ChCl:Lactic Acid (1:1) ChCl:Fructose (1:1) DFT B3LYP/6-311++G(d,p) CO 2 absorption by DES [ 79 ] 5 Alanine:Lactic acid (1:1) Betaine:Lactic acid (1:1) ChCl:Lactic acid (1:1) ChCl:Malic acid (1:1) ChCl:Phenylacetic acid (1:2) DFT B3LYP/6-311++G(d,p) High Pressure Methane Solubility in Natural DES [ 410 ] …”
Section: Table A1mentioning
confidence: 99%